Diagnosis : Official Journal of the Society to Improve Diagnosis in Medicine (SIDM) (De Gruyter, 2014)
Diagnosis aims at answering the question how diagnosis determines the quality of medical care. It focuses on how diagnosis can be advanced, how it is taught, and how and why it can fail, leading to diagnostic errors. The journal welcomes both fundamental and applied works, improvement initiatives, opinions, and debates to encourage new thinking on improving this critical aspect of healthcare quality.